Seedling establishment in a dynamic sedimentary environment: a conceptual framework using mangroves. Issue 3 (8th March 2013) - Balke, Thorsten; Webb, Edward L.; van den Elzen, Eva; Galli, Demis; Herman, Peter M. J.; Bouma, Tjeerd J.
Summary: Vegetated biogeomorphic systems (e.g. mangroves, salt marshes, dunes, riparian vegetation) have been intensively studied for the impact of the biota on sediment transport processes and the resulting self‐organization of such landscapes. However, there is a lack of understanding of physical disturbance mechanisms that limit primary colonization in active sedimentary environments. This study elucidates the effect of sediment disturbance during the seedling stage of pioneer vegetation, using mangroves as a model system. We performed mesocosm experiments that mimicked sediment disturbance as (i) accretion/burial of plants and (ii) erosion/excavation of plants of different magnitudes and temporal distribution in combination with water movement and inundation stress. Cumulative sediment disturbance reduced seedling survival, with the faster‐growing Avicennia alba showing less mortality than the slower‐growing Sonneratia alba . The presence of the additional stressors (inundation and water movement) predominantly reduced the survival of S. alba . Non‐lethal accretion treatments increased shoot biomass of the seedlings, whereas non‐lethal erosion treatments increased root biomass allocation. This morphological plasticity in combination with the abiotic disturbance history determined how much maximum erosion the seedlings were able to withstand. Synthesis and applications . Seedling survival in dynamic sedimentary environments is determined by the frequency and magnitude of sediment accretion or erosion events, with non‐lethal events causing feedbacks to seedling stability. Managers attempting restoration of mangroves, salt marshes, dunes and riparian vegetation should recognize sediment dynamics as a main bottleneck to primary colonization. The temporal distribution of erosion and accretion events has to be evaluated against the ability of the seedlings to outgrow or adjust to disturbances. Our results suggest that selecting fast‐growing pioneer species and measures to enhance seedling growth or temporary reduction in sediment dynamics at the restoration site can aid restoration success for vegetated biogeomorphic ecosystems. Abstract : Seedling survival in dynamic sedimentary environments is determined by the frequency and magnitude of sediment accretion or erosion events, with non‐lethal events causing feedbacks to seedling stability. Managers attempting restoration of mangroves, salt marshes, dunes and riparian vegetation should recognize sediment dynamics as a main bottleneck to primary colonization. The temporal distribution of erosion and accretion events has to be evaluated against the ability of the seedlings to outgrow or adjust to disturbances. Our results suggest that selecting fast‐growing pioneer species and measures to enhance seedling growth or temporary reduction in sediment dynamics at the restoration site can aid restoration success for vegetated biogeomorphic ecosystems.